Estudo e análise do processo corrosivo no açougue público da cidade de São Miguel/RN - Queiroz, Maria Gerlania de Oliveira (Universidade Federal Rural do Semi-Árido, 2018)
Corrosion is the process of deterioration that occurs with metallic materials as a result of their interaction with the medium, which causes the loss of material and consequently requires the replacement of unusable parts.This work investigated in a theoretical and comparative way the types of corrosion, present in the environment of the public butcher's shop, in the city of São Miguel, Rio Grande do Norte. The classification of the corrosive processes, based on the literature and construction of the corrosion triangle, for the environment in question were successfully applied to investigate the effects of exposure of meat to the metals present. The identification and later classification of the corrosion points helped to understand the results, which suggest to all corrosion processes the same triangle of corrosion. The comparative analyzes suggest the immediate replacement of corroded metal parts. The environment conducive to the formation of the corrosive atmosphere reveals environmental and structural factors that influence in the appearance of corrosion in the metals, which possibly cause a risk of contamination of the meat present.
Keywords: Corrosão; Concreto; Metal; Triângulo da corrosão; Corrosion; Concret; Metal; Corrosion Triangle; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA